Phyto-pharmacology of Hemidesmus indicus - Aneja, Vandana; Suthar, Ashish; Verma, Sonika; Kalkunte, Satyan (Pharmacognosy Reviews)
Plants have been the basis of many traditional medicines throughout the world for thousands of years and continue to provide new remedies to mankind. Plants are one of the richest sources of compounds. Hemidesmus indicus is one of the plants used in Ayurveda for several remedies. It is used as a tonic, alternative, demulscent, diaphoretic, and diuretic, in the treatment of syphilis, chronic rheumatism and urinary disorders. Scientific evidence suggests its versatile biological functions that support its traditional use in the orient. This review aims to highlight the ethnobotany, pharmacognostic and pharmacological uses of Hemidesmus indicus
Keywords: Hemidesmus indicus; phytochemical constituents; pharmacological actions; toxicity